Usefulness of Multimedia Instruction on Achievement in Commerce at Higher Secondary Level - R. , Padma; P.B. , Beulahbel Bency (International Journal of Psychosocial Rehabilitation, 2020)
Multimedia in education is a system for presenting information using a combination of images, sound, audio, and text. In the classroom, multimedia can connect the gap between theory and practice by giving students the opportunity to practice what they have learned in a safe and controlled environment. The school technology curriculum includes multimedia presentations as a required skill for students. This research article discusses how the multimedia program is used effectively with students studying commerce at the higher secondary level . The sample consisted of 903 higher secondary students from commerce using a simple random sampling technique. Data were analyzed, and it was found that the students who learned through the Multimedia Instructional Package performed better than those who learned through the traditional method of teaching.